Inspiration of Induced Magnetic Field on a Blood Flow of Prandtl Nanofluid Model with Stenosis - Nadeem, S.; Ijaz, Shagufta; Adil Sadiq, M. (Current Nanoscience, 2014)
In this paper, we have discussed the influence of induced magnetic field on a blood flow through an axissymmetric stenosed artery. The nature of blood is analyzed mathematically by treating it as Prandtl nanofluid. An analytical expression of velocity profile, nanoparticle volume fraction and temperature profile has been computed for mild stenosis by using the homotopy perturbation method. Physical features of resistance impedance, wall shear stress, wall shear stress at the stenosis throat, axial induced magnetic field and current density distribution have been discussed through graphs.
Keywords: Blood flow